2016
DOI: 10.1038/srep23110
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and prophylactic activity of itraconazole against human rhinovirus infection in a murine model

Abstract: Human rhinovirus (HRV) is the most common viral infectious agent in humans and is the predominant cause of the common cold. There is a need for appropriate vaccines or therapeutic agents to treat HRV infection. In this study, we investigated whether itraconazole (ICZ) can protect cells from HRV-induced cytotoxicity. Replication of HRV1B was reduced by ICZ treatment in the lungs of HRV1B- as compared to vehicle-treated mice. The numbers of immune cells, including granulocytes and monocytes, were reduced in bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…Unfortunately, PI4KB inhibition was found to be associated with adverse side effects 91,92 . OSBP inhibitors include the antifungal drug itraconazole (Sporanox) 93 , which was shown to have antiviral activity in mice 94 .…”
Section: Heterogeneous Nuclear Ribonucleoprotein Cmentioning
confidence: 99%
“…Unfortunately, PI4KB inhibition was found to be associated with adverse side effects 91,92 . OSBP inhibitors include the antifungal drug itraconazole (Sporanox) 93 , which was shown to have antiviral activity in mice 94 .…”
Section: Heterogeneous Nuclear Ribonucleoprotein Cmentioning
confidence: 99%
“…Other OSBP inhibitors (e.g., 25-hydroxycholesterol, AN-12-H5, T-00127-HEV2, TTP-8307, and the natural compound OSW-1) also impaired enterovirus replication [56,[63][64][65]. In a rhinovirus mouse model, prophylactic intranasal treatment with itraconazole reduced viral titers and pathology, raising expectations for topically applied itraconazole to prevent or treat common colds [66].…”
Section: Pi4kbmentioning
confidence: 99%
“…Recently, three novel epidithiodiketopiperazines (KCN-2,2’-epi-19, KCN-19 and KCN-21) were synthesized that displayed activity against RV-87 [ 33 ]. Interestingly, the antifungal compound itraconozole has recently been found to have in vitro and in vivo antiviral activity in RV infection [ 61 ]. This was potentially due to inhibition of cellular cholesterol trafficking, a process the authors suggest, in accord with another study [ 62 ], is essential for RV replication.…”
Section: Introductionmentioning
confidence: 99%
“…For example, both oxysterol binding protein (OSBP) and phosphatidylinositol 4-kinase III β (PI4KB), have been identified as host proteins involved in picornavirus replication [ 133 , 134 , 135 ], and studies focusing upon chemical inhibition of PI4KB with a panel of aminothiazoles have demonstrated potent inhibition of RV [ 136 ]. Equally, novel enviroxime-like compounds as well as other compounds such as itraconozole (mentioned above) which can target OSBP have also shown promise in inhibiting viral replication [ 61 , 62 , 134 , 137 ]. Furthermore, as both PI4KB and OSBP can act as substrates for protein kinase D (PKD), recent studies have identified PKD as a key molecule in RV replication and have demonstrated that PKD inhibition can profoundly affect RV replication at an early stage [ 138 ].…”
Section: Introductionmentioning
confidence: 99%